Novel Eye Movement Disorders in Whipple’s Disease—Staircase Horizontal Saccades, Gaze-Evoked Nystagmus, and Esotropia - Shaikh, Aasef G.; Ghasia, Fatema F. (Frontiers in Neurology, 2017)
Whipple’s disease, a rare systemic infectious disorder, is complicated by the involvement of the central nervous system in about 5% of cases. Oscillations of the eyes and the jaw, called oculo-masticatory myorhythmia, are pathognomonic of the central nervous system involvement but are often absent. Typical manifestations of the central nervous system Whipple’s disease are cognitive impairment, parkinsonism mimicking progressive supranuclear palsy with vertical saccade slowing, and upgaze range limitation. We describe a unique patient with the central nervous system Whipple’s disease who had typical features including parkinsonism, cognitive impairment, and upgaze limitation; but also had diplopia, esotropia with mild horizontal (abduction more than adduction) limitation, and vertigo. The patient also had gaze-evoked nystagmus and staircase horizontal saccades. Latter were thought to be due to mal-programmed small saccades followed by a series of corrective saccades. The saccades were disconjugate due to the concurrent strabismus. Also, we noted disconjugacy in the slow phase of gaze-evoked nystagmus. The disconjugacy of the slow phase of gaze-evoked nystagmus was larger during monocular viewing condition. We propose that interaction of the strabismic drifts of the covered eyes and the nystagmus drift, putatively at the final common pathway might lead to such disconjugacy.